2021
DOI: 10.3390/antiox10091488
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-Mediated Oxidative Stress Enhances Cystathionine γ-Lyase-Derived H2S Synthesis via a Sulfenic Acid Intermediate

Abstract: Hydrogen sulfide (H2S), which is generated mainly by cystathionine γ-lyase (CSE) in the cardiovascular system, plays a pivotal role in a wide range of physiological and pathological processes. However, the regulatory mechanism of the CSE/H2S system is poorly understood. Herein, we show that oxidation induces the disulfide bond formation between Cys252 and Cys255 in the CXXC motif, thus stimulating the H2S-producing activity of CSE. The activity of oxidized CSE is approximately 2.5 fold greater than that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The free thiol group in cysteine can be easily oxidized to sulfenic, sulfinic, and sulfonic acids, thus changing the activities of enzymes [34]. In cultured smooth muscle cells, H 2 O 2 incubation did not change the mRNA and protein levels of CSE but was able to promote the activity of CSE and increase H 2 S production [35]. However, in another study with human umbilical vein endothelial cells, H 2 O 2 suppressed H 2 S generation by directly reducing CSE protein expression [36].…”
Section: Discussionmentioning
confidence: 97%
“…The free thiol group in cysteine can be easily oxidized to sulfenic, sulfinic, and sulfonic acids, thus changing the activities of enzymes [34]. In cultured smooth muscle cells, H 2 O 2 incubation did not change the mRNA and protein levels of CSE but was able to promote the activity of CSE and increase H 2 S production [35]. However, in another study with human umbilical vein endothelial cells, H 2 O 2 suppressed H 2 S generation by directly reducing CSE protein expression [36].…”
Section: Discussionmentioning
confidence: 97%
“…In males, 3 weeks of DD exposure resulted in alterations in glycine, serine, and threonine metabolism (cystathionine, sarcosine and glycerate) and ketone body metabolism (acetoacetate) (Figure 6a and Table S4). Previous studies have reported modulation of these pathways and metabolites in stress‐related psychiatric disorders (Chen et al, 2017; Wang et al, 2021; Yang et al, 2013). In females, 3 weeks of DD exposure modulated phenylalanine tyrosine and tryptophan metabolism (phenylalanine and phenylacetate metabolites), which are involved in synthesising neurotransmitters such as dopamine and norepinephrine (Figure 6B and Table S4).…”
Section: Discussionmentioning
confidence: 97%
“…Our past studies have demonstrated for the first time the antiviral and anti-inflammatory role of CSE/H 2 S both in vitro and in vivo, following in RSV infection [ 2 , 3 ]. The expression of CSE has not been extensively investigated, but it is known to be regulated by oxidative stress, as in the case of H 2 O 2 cell stimulation [ 23 ]. The transcription of many oxidative stress-inducible genes is regulated in part through cis -acting ARE sequences.…”
Section: Discussionmentioning
confidence: 99%